The relation of sensitivity to provocation and frustration to direct aggression: the mediating role of beliefs about aggression / La relación entre la sensibilidad a la provocación y a la frustración y la agresión directa: el papel mediador de las creencias sobre la agresión. Issue 1 (2nd January 2018) - Konopka, Karolina; Zajenkowska, Anna; Dominiak-Kochanek, Monika
Abstract: Previous research has suggested that sensitivity to provocation and frustration differently predict aggressive behaviour. In the study reported in this paper, two potential mediators of the relationships among both sensitivities and self-reported aggression were examined, namely instrumental and expressive beliefs about aggression. A sample of 318 participants (52% men) took part in the study. Structural Equation Modeling demonstrated that sensitivity to provocation was related to both types of beliefs about aggression, whereas sensitivity to frustration was associated with expressive beliefs. However, only instrumental beliefs mediated the relationship between sensitivity to provocation and both physical and verbal aggression. Analysed variables predicted 46% of the variance in physical aggression and 11% of the variance in verbal aggression. Additionally, men reported higher physical aggression and endorsed more instrumental beliefs than women. Implications for understanding emotional and cognitive mechanisms involved in regulation of aggression are discussed.